Iowa CBC reporting form, Rathbun, December 21, 1985 - Heusinkveld, Billet al (1985)
Checklist dated December 21, 1985 compiled by Bill Heusinkveld. A list of birds sighted by Heusinkveld and twenty-three others around Rathbun Lake. A total of 60 species and 5,969 individual birds were sighted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Winter 1985-1986. Epson - sheet feed